The Impact of Values 1998
DOI: 10.1093/0198294751.003.0011
|View full text |Cite
|
Sign up to set email alerts
|

Postmodernism

Abstract: This chapter has two aims: first, to show how post‐modern theory helps explain contemporary value changes in Western Europe, and their impact on beliefs about the role and legitimacy of government; second, to demonstrate how the concept of post‐modernism can be operationalized and put to empirical use. It hypothesizes the emergence of new ‘structures of feeling’ and new formations of values, which are united by little else than a common yearning for identity and self‐expression. This hypothesis implies that, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 131 publications
0
4
0
Order By: Relevance
“…Following the efforts of Wildavsky and Dake (1990), it is therefore not surprising at all that the strategy of measuring grid-group theory's biases in surveys was tested and developed by others (Jenkins- Smith and Smith, 1994;Sjöberg, 1995;Peters and Slovic, 1996;Ellis and Thompson, 1997;Marris et al, 1998;Coughlin and Lockhart, 1998;Grendstad, 2000Grendstad, , 2001Grendstad and Selle, 2000). Over time, survey analysts have persuasively shown, in a number of studies, that socio-demographic variables are significant correlates of materialist-postmaterialist value orientations (Scarbrough, 1995;Schweisguth, 1995), left-right materialist value orientations (Knutsen, 1995a;Schweisguth, 1995), religious cognitions and beliefs Pettersson and Riis, 1994;Riis, 1994;Sundback, 1994Sundback, , 2000Dobbelaere, 1995;Schweisguth, 1995;Dobbelaere and Jagodzinski, 1995;Gustafsson and Pettersson, 2000), environmentalism (Lowe and Rüdig, 1986;Jones and Dunlap, 1992;Ester et al, 1994b;Kanji and Vevitte, 1996;Zelezny et al, 2000), social libertarianism (Schweisguth, 1995), post-modernism (Gibbins and Reimer, 1995), racism (Jasinska-Kania, 1999), as well as other sundry dimensions (Harding et al, 1986;Gundelach, 1991;Broek and Heunks, 1994;Listhaug, 1995;…”
Section: Grid-group Theory and Value Surveysmentioning
confidence: 99%
“…Following the efforts of Wildavsky and Dake (1990), it is therefore not surprising at all that the strategy of measuring grid-group theory's biases in surveys was tested and developed by others (Jenkins- Smith and Smith, 1994;Sjöberg, 1995;Peters and Slovic, 1996;Ellis and Thompson, 1997;Marris et al, 1998;Coughlin and Lockhart, 1998;Grendstad, 2000Grendstad, , 2001Grendstad and Selle, 2000). Over time, survey analysts have persuasively shown, in a number of studies, that socio-demographic variables are significant correlates of materialist-postmaterialist value orientations (Scarbrough, 1995;Schweisguth, 1995), left-right materialist value orientations (Knutsen, 1995a;Schweisguth, 1995), religious cognitions and beliefs Pettersson and Riis, 1994;Riis, 1994;Sundback, 1994Sundback, , 2000Dobbelaere, 1995;Schweisguth, 1995;Dobbelaere and Jagodzinski, 1995;Gustafsson and Pettersson, 2000), environmentalism (Lowe and Rüdig, 1986;Jones and Dunlap, 1992;Ester et al, 1994b;Kanji and Vevitte, 1996;Zelezny et al, 2000), social libertarianism (Schweisguth, 1995), post-modernism (Gibbins and Reimer, 1995), racism (Jasinska-Kania, 1999), as well as other sundry dimensions (Harding et al, 1986;Gundelach, 1991;Broek and Heunks, 1994;Listhaug, 1995;…”
Section: Grid-group Theory and Value Surveysmentioning
confidence: 99%
“…In other words, we see change as the equation of the dialectic between the modern and the postmodern rather than a specific developmental process moving towards the postmodern society (cf. Gibbins and Reimer 1995) and leaving the modern, or the pre-modern, behind. In any case, the mere existence of postmodernism is itself an indication of potential change (cf.…”
Section: Modern Versus Postmodern Politicsmentioning
confidence: 99%
“…Apparently, the follow-up telephone survey resulted in lower internal consistency reliability than did the earlier face-to-face survey. Items for the measures came from various sources (Broaded et al, 1994;Gibbins & Reimer, 1995;Inglehart, 1997, Inkeles, 1993Seippel, 1999). Measures of satisfaction with life These included one for life in general, one for cultural conditions (including local cultural atmosphere, relationship with the family, community environment, and leisure activity), one for economic conditions (including local economic conditions, financial conditions, work conditions, and local development), and one for political conditions (including government policy, government performance, government structure, and local political situation).…”
Section: Measurementmentioning
confidence: 99%
“…Postmaterialist values include having more say in government decisions, a more humane society, protecting freedom of speech, progressing toward a society in which ideas count more than money, having more say about how things are done at jobs, and making cities and the countryside more beautiful. Postmodern values include romantic life, absence of truth, no need for a commodity to have value, no need for work to be useful to society, no need for money, no need for material possession, development of human qualities, free expression, expression of unique characters, and showing off one's character (Broaded, Cao & Inkeles, 1994;Gibbins & Reimer, 1995;Seippel, 1999). Research has shown that younger and wealthier people are more postmaterialistic than older people (Clarke, 2000).…”
mentioning
confidence: 99%